An Augmented Method for Collecting PLGA Nanoparticles and the Fabrication of 1, 3, 4, 6-Tetra-O-acetyl-2-azido-2-deoxy-D-glucopyranose (Ac42AzGlc)-Loaded PLGA Nanoparticles for Efficient and Prospective in Vivo Metabolic Processing - Parashar, Shubham; Chauhan, Charu; Rajasekharan, Abhiraj; Rautela, Jyoti; Jain, Tanya; Raza, Kaisar (Frontiers in Bioengineering and Biotechnology, 2022)
We investigated two ways for fabricating 1, 3, 4, 6-tetra-O-acetyl-2-azido-2-deoxy-D-glucopyranose (Ac42AzGlc)-loaded poly (lactic-co-glycolic acid) PLGA nanoparticles in this manuscript: i.e (i) single emulsion solvent evaporation and (ii) nanoprecipitation method. Among the available methods of collecting nanoparticles using ultra-high-speed centrifuge, we improvised a less known method for collecting synthesised nanoparticles without a high-speed centrifuge, based on molecular weight (MW) dependent centrifugal filters. These nanoparticles were collected in a tabletop centrifuge at a meagre centrifugal force in the range of 200-300 xg. The conventional high-speed centrifuge method for nanoparticle recovery, results in a hard nanoparticle pellet with poor re-suspendability which hampers the yield and outcomes of the product. The Ac42AzGlc loaded PLGA nanoparticles were spherical in shape with consistent and reliable nanometric particle size. The polydispersity indices were well within the acceptable limits. The preliminary studies in RAW 264.7 cell and C57BL/6 mice advocated efficient engineering in the former, however the later needs further confirmatory investigations. Preliminary in vivo studies with un-encapsulated Ac42AzGlc showed poor engineering of cardiac glycoproteins, opening up avenues for Ac42AzGlc loaded nanoparticles for improved bioavailability and efficient metabolic engineering.